Pengukuran Kaji Dampak pada Program Pemberdayaan Petani Kopi di Tapanuli Selatan - Rina Ekawati; Ari Djanuar Prasetyo; Suesilowati Suesilowati (Bulletin of Community Engagement, 2023)
The article discusses the Measurement of Impact Assessment on the Coffee Farmer Empowerment Program in South Tapanuli. Data collection techniques were obtained from in-depth interviews, FGDs and direct observation of all relevant stakeholders. The data results are used as a unitary material together with the SROI calculation. SROI is currently the most generally accepted way of explaining the monetary value of the social, economic and health outcomes of an initiative. Social return on investment (SROI) is a framework used to measure and account for the value created by a program or series of initiatives, beyond financial value. In order to calculate the benefit to cost ratio, SROI uses monetary values to represent social, economic and health outcomes. For example, the 4:1 ratio in the SROI analysis shows that an investment of IDR 1 generates IDR 4 of social value. Based on the results of the SROI calculation, the SROI ratio reached 1: 2.29. This ratio means that every IDR 1 invested in the Iron Green House program is capable of producing a social impact of IDR 2.29. As a new initiative in the implementation of the TJSL program that departs from environmental issues, the number of these ratios is large enough to produce social impacts. Keywords: Coffee Farmer Empowerment Program, Environmental Issues, Economic Outcomes, Social Impacts